(untitled) (Fiep Bulletin - online, 2017)
In recent decades the study of the brain had intensive development and eventually set up a multifaceted field ofknowledge called Neuroscience. These advances, in addition to bringing down myths, revealed big surprises that have beenassimilated by various human activities, from medicine to marketing. However, in the field of education and specifically inPhysical Education, this appropriation is still incipient, particularly as regards the relationship between Motricity and Learning,Motricity and Health and Health Promotion. Thus, the search test this problematize some contributions to the field ofneuroscience brings to the Education and Physical Education, but are still little known and used.